Within-person variability and couple synchrony in state relationship satisfaction: testing predictors and implications - Scheling, Louisa; Wrzus, Cornelia; Weidmann, Rebekka; Burriss, Robert Philip; Wünsche, Jenna; Grob, Alexander; Bühler, Janina Larissa (Journal of personality and social psychology, 2025)
To better understand romantic relationship development, research has focused on how trait relationship satisfaction develops across months and years. However, because romantic relationships evolve in daily life, it is critical to also examine state relationship satisfaction and its fluctuations across and within days. In this preregistered study, we examined how strongly romantic partners vary in their state relationship satisfaction (within-person variability) and how synchronous they are in their variability (couple synchrony). Moreover, we focused on predictors (demographic, personality, and relationship characteristics) and implications (trait relationship satisfaction, stability) of variability and synchrony. We used two dyadic data sets of female-male couples, including 593 couples in Study 1 and 150 couples in Study 2. State relationship satisfaction was assessed daily in a multiwave diary study (Study 1) and multiple times a day in an experience sampling study (Study 2). The results of dynamic structural equation modeling indicated that individuals varied significantly in their state relationship satisfaction, with higher variability across than within days, and that couple synchrony was moderate to high. Key predictors of variability were both partners’ perceived responsiveness and men’s neuroticism, while the main predictor of couple synchrony was women’s perceived responsiveness. Higher variability was related to lower trait relationship satisfaction, but variability and synchrony had no long-term implications for relationship satisfaction and stability. Together, these findings provide a granular view on romantic relationships, suggesting that variability in state relationship satisfaction is common to most romantic relationships. High variability, however, may be an indicator of unmet needs in the relationship. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 06.11.2025